Chronic Primary Pain in Children and Young People: Evidence Review with Reference to Safeguarding. (15th November 2021) - Gauntlett-Gilbert, Jeremy; Rogers, Valerie; Menzies, Mike; Connell, Hannah
Abstract: Many children and young people experience recurrent pain, and a minority of these experience substantial disability and distress. Some have pain that is intrusive and that does not come from an obvious medical cause, such as chronic abdominal pain, headache or widespread musculoskeletal pain. Historically, such persisting pain has been a contested category, with labels such as 'psychosomatic' or 'medically unexplained' pain being used. Social Workers are not always able to access unequivocal medical advice about treatment and prognosis in these conditions and will benefit from being aware of the current literature. Happily, contemporary research helps to explain the physiological origin of such chronic pain states, and the personal and systemic contributors to pain-related distress and disability. This paper reviews epidemiology, cause, presenting features and treatment of these conditions, as well as issues of stigma. Successful investigation of child safeguarding concerns in this context, and of suspected fabricated and induced illness, will benefit from an understanding of the typical presentation of these conditions, as they are not well understood in mainstream medical practice. We explore how parental attitudes and actions may sometimes come from legitimate concerns, yet may also in some situations come to constitute cause for safeguarding concern. Abstract : Some young people have a chronic primary pain (CPP) condition, where they experience unpleasant ongoing pain despite there being no cause easily found by doctors. Some examples would be persistent stomach pain, headache or muscle and joint pain. Most people do not understand these conditions, including Social Workers but also most health and education professionals. This makes things harder when a Social Worker needs to support a young person with pain, or where they need to investigate child safeguarding concerns. This paper reviews literature that explains how CPP conditions can arise, what young people usually struggle with and how to distinguish family factors that are common from those that may indicate safeguarding concern.